2020
DOI: 10.3390/ijms21134809
|View full text |Cite
|
Sign up to set email alerts
|

Silencing of TaCKX1 Mediates Expression of Other TaCKX Genes to Increase Yield Parameters in Wheat

Abstract: TaCKX, Triticum aestivum (cytokinin oxidase/dehydrogenase) family genes influence the development of wheat plants by the specific regulation of cytokinin content in different organs. However, their detailed role is not known. The TaCKX1, highly and specifically expressed in developing spikes and in seedling roots, was silenced by RNAi-mediated gene silencing via Agrobacterium tumefaciens and the effect of silencing was investigated in 7 DAP (days after pollination) spikes of T1 and T2 generations. Vari… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
51
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(72 citation statements)
references
References 74 publications
5
51
0
Order By: Relevance
“…Our results showing coordinated regulation of the GSKs in barley provide novel data on the mechanisms of BR homeostasis in plants. A similar data, concerning RNAi-based silencing of TaCKX1 and associated with this co-regulation of CKX paralogs, were reported by Jablonski et al [52]. The authors found that diverse levels of target gene silencing were associated with different models of co-expression with other TaCKX genes and parameters of yield-related traits in wheat.…”
Section: Discussionsupporting
confidence: 78%
“…Our results showing coordinated regulation of the GSKs in barley provide novel data on the mechanisms of BR homeostasis in plants. A similar data, concerning RNAi-based silencing of TaCKX1 and associated with this co-regulation of CKX paralogs, were reported by Jablonski et al [52]. The authors found that diverse levels of target gene silencing were associated with different models of co-expression with other TaCKX genes and parameters of yield-related traits in wheat.…”
Section: Discussionsupporting
confidence: 78%
“…Some functions of these genes might also be predicted by known function of their orthologues in other cereal species. Silencing of HvCKX1 orthologous to TaCKX1 resulted in elevated grain number in these two, closely related species [9,11]. However, the same effect of increased grain number in rice was obtained by silencing or knocking-out OsCKX2 [30].…”
Section: Introductionmentioning
confidence: 92%
“…Only some TaCKX GFMs are functionally characterized. Silencing of TaCKX1 by RNAi influenced levels of expression of the other TaCKX GFMs, and increased content of most CK forms and GA 3 , which caused an increase of yield parameters such as a higher spike number, grain number, and grain yield, but lower thousand grain weight [11]. The effect of TaCKX2.4 gene silencing by RNAi increased grain number per spike [34].…”
Section: Introductionmentioning
confidence: 99%
“…Targeting cytokinin homeostasis through the application of exogenous compounds leads to a range of effects that are frequently inconsistent [ 68 ], which supports suggestions that cytokinin homeostasis is complex and tightly regulated. It is well known that targeting CKX with CKX-inhibiting PGRs has an effect on cytokinin homeostasis and/or cytokinin-associated processes [ 44 , 45 , 46 , 47 , 48 , 49 ], including INCYDE [ 34 , 51 , 52 , 54 , 56 ] and through targeting CKX in mutants and/or transgenic plants [ 36 , 37 , 38 , 39 , 41 , 42 , 69 ].…”
Section: Discussionmentioning
confidence: 99%
“…Inhibition of CKX has been suggested as a strategy for enhancing endogenous cytokinin to enhance growth [ 34 ] and yield [ 31 , 35 ]. This approach has been successful in enhancing yield components with ckx double mutants in Arabidopsis thaliana (Arabidopsis) [ 36 ] and oil seed rape [ 37 ], OsCKX2 loss-of-function mutants with rice [ 38 ], and RNAi gene silencing of HvCKX1 in barley [ 39 , 40 ], and TaCKX1 in wheat [ 41 ]. Notably, experiments with RNA-guided Cas9 ckx mutant lines in barley have shown that single CKX gene knockouts might be insufficient for enhancing yield [ 42 ].…”
Section: Introductionmentioning
confidence: 99%